School Digitalization Policy in Banyuwangi: A Literature-Based Analysis of Its Effectiveness in Addressing Digital Inequality - Lidia Astuti; Safarotul Jannah; Nur Anim Jauhariyah (ICO EDUSHA, 2025)
Digital transformation in the education sector is the Indonesian government's strategic agenda in responding to learning challenges in the technological and post-pandemic era. Banyuwangi Regency, as one of the regions that is actively encouraging the digitalization of public services, is also implementing school digitalization policies through the use of online learning platforms, Learning Management Systems (LMS), and various digital education applications. However, the implementation of this policy has given rise to academic debate regarding its effectiveness in reducing inequality in access to digital learning between schools. This research aims to critically analyze the effectiveness of school digitalization policies in Banyuwangi in overcoming digital inequality through a literature review approach. The research method used is a literature study by examining national and international journal articles, government policy documents, institutional reports, and online publications that are relevant to the topic of educational digitalization and the digital divide. The results of the study show that school digitalization policies have great potential in increasing learning flexibility and educational management efficiency, but are not yet fully able to overcome digital inequality due to differences in infrastructure, teachers' digital literacy capacity, and students' socio-economic readiness. Therefore, a more inclusive and sustainable policy strategy is needed so that the digitalization of education is not only a symbol of modernization, but also a means of equal access and justice to education. Keywords : School Digitalization, Education Policy, Digital Inequality, Online Learning, Banyuwangi